2019
DOI: 10.1097/dcr.0000000000001281
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Nonsteroidal Anti-inflammatory Drugs to Improve GI Recovery After Colorectal Surgery

Abstract: Background: The management of delayed gastrointestinal recovery after surgery is an unmet challenge. Uncertainty over its pathophysiology has limited previous research, but recent evidence identifies intestinal inflammation and activation of mu-opioid receptors as key mechanisms. Non-steroidal anti-inflammatory drugs (NSAIDs) are recommended by enhanced recovery protocols for their opioid-sparing and anti-inflammatory properties. Objectives: To explore the safety and efficacy of NSAIDs to improve gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…NSAIDs are recommended by enhanced recovery protocols to optimize pain management and to reduce opioid‐related adverse effects. They may also improve the recovery of bowel function; a recent meta‐analysis of high‐quality RCTs demonstrated that NSAIDs reduce the times to first flatus and stool by 18 and 10 h respectively. The mechanism for this is unclear, but current evidence suggests a combination of decreased μ‐receptor agonism and inhibition of COX enzymes, which reduce neuromuscular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSAIDs are recommended by enhanced recovery protocols to optimize pain management and to reduce opioid‐related adverse effects. They may also improve the recovery of bowel function; a recent meta‐analysis of high‐quality RCTs demonstrated that NSAIDs reduce the times to first flatus and stool by 18 and 10 h respectively. The mechanism for this is unclear, but current evidence suggests a combination of decreased μ‐receptor agonism and inhibition of COX enzymes, which reduce neuromuscular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…These may have benefits for the recovery of gastrointestinal function. Recent meta‐analyses of RCTs demonstrated a significant pooled benefit of NSAIDs in reducing ileus after colorectal surgery. However, the use of NSAIDs in this setting is controversial owing to the risk of acute kidney injury and conflicting reports of increased anastomotic leak rates.…”
Section: Introductionmentioning
confidence: 99%
“…93 Metaanalysis of RCTs concluded that COX2 inhibitors significantly improved time to gut recovery after elective colorectal surgery 99 and that the "drugs may represent an effective and accessible intervention to improve GI recovery". 100 A key point is that, unlike the Wattchow study, 25 preoperative dosing was not included in all studies. 100 The meta-analysis also showed the drugs to be safe in terms of renal function and rates of anastomotic leak (Level 1 evidence).…”
Section: Cyclooxygenase Inhibitorsmentioning
confidence: 99%
“…100 A key point is that, unlike the Wattchow study, 25 preoperative dosing was not included in all studies. 100 The meta-analysis also showed the drugs to be safe in terms of renal function and rates of anastomotic leak (Level 1 evidence).…”
Section: Cyclooxygenase Inhibitorsmentioning
confidence: 99%
“…Parenteral formulations of ketorolac and ibuprofen are the only IV NSAIDs currently approved for postoperative pain management in the US [16]. Studies have found that ketorolac reduces opioid consumption by 25-45% and provides additional bene ts such as improving bowel function after colorectal surgery and epidural pain after cesarean delivery [17][18][19]. Intravenous ibuprofen is approved for the management of mild to moderate pain and for the management of moderate to severe pain as an adjunct to opioid analgesics [20].…”
Section: Introductionmentioning
confidence: 99%